ШАХС КАМОЛОТИДА ИЖТИМОИЙ ОМИЛЛАРНИНГ ЎРНИ (Scientific journal of the Fergana State University, 2023)
In this article the role of social-spiritual factors, in other words, some problems like the social-aesthetic gist of independence in the upbringing of perfect generation are considered.